The Dynamics of Employee Performance: Motivation and Discipline Perspectives - Susan Ridwan; Jusdijachlan (Greenation Research & Yayasan Global Resarch National, 2023)
In the Secretariat of the Regional Representative Council (DPRD) of West Java Province, the study aims to simultaneously and partially investigate and analyze: (1) motivation; (2) work discipline; (3) employee performance; and (4) the effect of work motivation and discipline on employee performance. The staff at the Secretariat of the Regional Representative Council (DPRD) of West Java Province served as the unit of analysis in this study, with a sample size of 60 people. Frequency distribution and path analysis were used as the analytical techniques. The Secretariat of the Regional Representative Council (DPRD) of West Java Province's employees were deemed to have a high level of motivation, a high level of discipline, and a high level of employee performance based on the findings of the research and debate. Employee performance is influenced by both motivation and discipline at the same time, but motivation has a somewhat stronger influence than work discipline.